IL-21 Biased Alemtuzumab Induced Chronic Antibody-Mediated Rejection Is Reversed by LFA-1 Costimulation Blockade - Kwun, Jean; Park, Jaeberm; Yi, John S.; Farris, Alton B.; Kirk, Allan D.; Knechtle, Stuart J. (Frontiers in Immunology, 2018)
Abstract Despite its excellent efficacy in controlling T cell mediated acute rejection, lymphocyte depletion may promote a humoral response. While T cell repopulation after depletion has been evaluated in many aspects, the B cell response has not been fully elucidated.We tested the hypothesis that the mechanisms also involve skewed T helper phenotype after lymphocytic depletion. Post-transplant immune response was measured from alemtuzumab treated hCD52Tg cardiac allograft recipients with or without anti-LFA-1 mAb. Alemtuzumab induction promoted serum DSA, allo-B cells, and CAV in humanized CD52 transgenic (hCD52Tg) mice after heterotopic heart transplantation. Additional anti-LFA-1 mAb treatment resulted in reduced DSA (Fold increase 4.75±6.9 vs. 0.7±0.5; p<0.01), allo-specific B cells (0.07±0.06 vs.0.006±0.002 %; p<0.01), neo-intimal hyperplasia (56±14% vs. 23±13%; p<0.05), arterial disease (77.8±14.2 vs. 25.8±20.1%; p<0.05), and fibrosis (15±23.3 vs. 4.3±1.65%; p<0.05) in this alemtuzumab-induced chronic antibody-mediated rejection (CAMR) model. Surprisingly, elevated serum IL-21 levels in alemtuzumab-treated mice was reduced with LFA-1 blockade. In accordance with the increased serum IL-21 level, alemtuzumab treated mice showed hyperplastic germinal center (GC) development, while the supplemental anti-LFA-1 mAb significantly reduced the GC frequency and size. We report that the incomplete T cell depletion inside of the GC leads to a systemic IL-21 dominant milieu with hyperplastic GC formation and CAMR. Conventional immunosuppression, such as tacrolimus and rapamycin, failed to reverse AMR, while co-stimulation blockade with LFA-1 corrected the GC hyperplastic response. The identification of IL-21 driven chronic AMR elucidates a novel mechanism that suggests a therapeutic approach with cytolytic induction.